Incorporation of Rice Husk Ash with Palm Oil Mill Wastes in Enhancing Physicochemical Properties of the Compost - Nur Eliza, Badrul Hisham; Nor Hanuni, Ramli (Universiti Putra Malaysia Press, 2021)
Rice husk ash (RHA), palm oil mill effluent (POME) sludge and decanter cake can be utilized together in compost production to minimize the environmental pollution. This study aims to evaluate the role of different composition of RHA in enhancing the physicochemical properties of palm oil-based compost. The composts were prepared by mixing different composition of RHA, in the range of 0% to 30%, with 1:1 (wt/wt) weight ratio of POME sludge and decanter cake. The moisture content, water holding capacity, pH, nitrogen (N), phosphorus (P), potassium (K), silica (Si) contents, and C:N ratio of raw materials were analyzed by using CHNS and WDXRF analyzers. The composting process was conducted in compost containers for 60 days, in which the temperature and pH of the composts were monitored daily. The finished composts were analyzed for physicochemical properties as same as raw materials. For physical properties of finished composts, RHA30 had the highest moisture content and water holding capacity which was 1.9 to 23.8% (wt/wt) and 4.2 to 26.8% higher compared to other finished composts, respectively. For chemical properties, the highest N and P contents were recorded by control compost. However, for K and Si content, the elements were found to be higher in RHA10 and RHA30, respectively, compared to other finished composts. Overall, RHA, POME sludge and decanter cake combination in compost production can create a well-balanced condition for the compost to perform effectively as an organic fertilizer. The addition of 5% to 10% RHA in compost formulation made from palm oil mill wastes is suggested to achieve the desirable condition.